Presentations for The EU Deforestation Regulation: Policy Implications and Research Frontiers - Leimona, Beria; Gmeiner, Simon; Hadi, Andri; Suparyono, Mohd Hasbollah; Piñeiro, Valeria; Chen, Kevin Z.; Salleh, Izzana; Adams, Vanessa; Durango, Sandra (International Food Policy Research Institute, 2025)
In June 2023, the European Union (EU) adopted its Regulation on Deforestation-Free Products (EUDR)—a landmark policy designed to reduce global deforestation and forest degradation driven by EU consumption. Under the regulation, key commodities with the biggest impacts on deforestation—soy, cattle, palm oil, cocoa, coffee, wood, and natural rubber—cannot be placed on the EU market or exported unless they are free of deforestation and legally produced.